Espectroscopias Raman e infravermelho em cristais de aminoácidos: os casos da L-valina e do ácido L-glutâmico - Fernandes, César Rodrigues (2015)
Studying the behavior of amino acids when exposed to extreme temperature conditions is the main objetive of this thesis. In the L-valine (C5H11NO2) infrared absorption measurements were performed, while Raman scattering measurements were performed in α and β forms of L-glutamic acid (C2H9NO4). On the L-valine, the infrared apparatus allowed two types of measurements: the former the interval was ~10 to ~700 cm ̄ ¹ (comprising the far-infrared region); the latter the range was 370 – 4000 cm ̄ ¹ (encompassing the region known as mid-infrared, the thermodynamic parameter temperature assumed values between 100 K and 300 K spaced apart by 20 K. In the Raman measurements one has been got a spacing of 50 K with a temperature ranging from 18 to 300 K for both the α phase and β phase. In the β phase, several scattering geometries were used; For the Raman measurements only one scattering geometry were performed on the α phase. In the L-valine spectra were observed appearances and disappearances of modes in the far infrared region (FAR-IR). A mode in 103 cm ̄ ¹ after behave in a regular way during the cooling process, unfolds in two modes quickly, and diferente from that expected by the spectral evolution Ꞷ x Ͳ. Opposite situation occurs when two modes colapse in 163 cm ̄ ¹ and, interestingly, at the same temperature as the unfolding: ~120K. Under the same conditions two modes, in ~211 cm ̄ ¹ and ~216 cm ̄ ¹ are reduced to a single mode in ~214 cm ̄ ¹. A peak in ~190 cm ̄ ¹ disappears in the range 100-120 K. In this range we can also check the large deviations from linearity of the frequencies of the modes in 147, 196, 225 and 305 cm ̄ ¹. Further, the vibrational modes in 154 cm ̄ ¹ and 214 cm ̄ ¹ exhibit discontinuities (in this case they were found between 120 and 160 K). This suggests it is not simple conformational changes, since such events (splits, disappearances and Strong nonlinearities modes) occurs in a particular temperature range. It can be concluded from this that the Crystal structure undergoes a phase transition that starts at 120 K and is complete at 100 K. Note that for the MID region, L-valine has not significant spectral changes: the frequencies of the modes are linear as whole, constant and without discontinuities. Raman measurements in the β formo f L-glutamic acid resulted in a constant number of vibration modes in the region of network modes during the cooling, what was interpreted as stability of the material. However, there was colapse (e.g.: ~500 cm ̄ ¹, 120 K, Z(XX)Z; three modes became two modes) and mode appearances (e.g: ~930 cm ̄ ¹, 120 K, Z(XX)Z; a mode becomes two modes) in other regions of the spectrum. Such events were interpreted as molecular environment changes (~930 cm ̄ ¹), “aliasing” effect that difficult the adjustment by Lorentzian functions (eg .: ~1070 cm ̄ ¹), and conformational chanfes. Such behaviors are not related to increments or decrements on defeneracy, so they suggest the stability of L-glutamic acid in the β form. The Raman spectra obtained for the α form of L-glutamic acid were completely regular: linear modes, without discontinuities on the frequencies or number of modes. From all the results, we seek to understand what factors determine the stability of na amino acid Crystal. The behavior of this Family of materials shows three “levels” of stability (i) stable (e.g.: L-glutamic acid and L-isoleucine), (ii) conformational micro-transitions (complex vibrational behavior, e.g: L-alanine) and (iii) crystals that undergo structural phase transition (e.g.: L-valine and L-leucine). Factors such as side chains ordering, van der Waals forces and average length of the hydrogen bonds (d̄LH) may influence the stability: L-valine and taurine undergo transition (d̄LH L –val = 2.92 Å, d̄LH tau = 2.90 Å), L-alanine → conformational micro-transition (d̄LH L –ala = 2.83 Å) and L-glutamic acid stable d̄LH L –glu(α) = 2.771 Å, d̄LH L –glu(β) = 2.798 Å. Note that: d̄LH L –glu(α, β) < d̄LH L –ala < d̄LH L –val’ d̄LH tau. L-theonine is na exception because it is stable although it has d̄LH L –treo = 2.86 Å. Other experimental techniques (eg: diffraction and nêutron scattering) are suggested to be used in the future in addressing this problem.